Modulation of plant root growth by nitrogen source‐defined regulation of polar auxin transport. (5th January 2021) - Ötvös, Krisztina; Marconi, Marco; Vega, Andrea; O'Brien, Jose; Johnson, Alexander; Abualia, Rashed; Antonielli, Livio; Montesinos, Juan Carlos; Zhang, Yuzhou; Tan, Shutang; Cuesta, Candela; Artner, Christina; et al.
Abstract: Availability of the essential macronutrient nitrogen in soil plays a critical role in plant growth, development, and impacts agricultural productivity. Plants have evolved different strategies for sensing and responding to heterogeneous nitrogen distribution. Modulation of root system architecture, including primary root growth and branching, is among the most essential plant adaptions to ensure adequate nitrogen acquisition. However, the immediate molecular pathways coordinating the adjustment of root growth in response to distinct nitrogen sources, such as nitrate or ammonium, are poorly understood. Here, we show that growth as manifested by cell division and elongation is synchronized by coordinated auxin flux between two adjacent outer tissue layers of the root. This coordination is achieved by nitrate‐dependent dephosphorylation of the PIN2 auxin efflux carrier at a previously uncharacterized phosphorylation site, leading to subsequent PIN2 lateralization and thereby regulating auxin flow between adjacent tissues. A dynamic computer model based on our experimental data successfully recapitulates experimental observations. Our study provides mechanistic insights broadening our understanding of root growth mechanisms in dynamic environments. SYNOPSIS: Effective soil exploitation by plants depends on rapid adjustment of root systems to available nutrients. Here, root growth adaptation to distinct nitrogen sources is shown to involve modulation of auxin distribution via phosphorylation of the PIN2 auxin carrier. Nitrogen source type (nitrate vs. ammonium) differentially regulates cell elongation and division patterns in Arabidopsis root tip tissues. Nitrogen source type regulates directionality of auxin transport in the root tip. Root growth adjustment to nitrogen source is mediated by PIN2 phosphorylation at S439. PIN2 phosphorylation affects auxin flux via modulation of PIN2 polarized localization at the plasma membrane. Abstract : Arabidopsis roots adjust their growth to the type of nitrogen source via phosphorylation of auxin carrier PIN2 and adjustment of auxin distribution between neighboring tissues.